Catalyst design for maximizing C5+ yields during Fischer-Tropsch synthesis - Hodala, Janardhan L.; Moon, Dong J.; Reddy, Kakarla Raghava; Reddy, Ch Venkata; Kumar, T. Naveen; Ahamed, Mohd Imran; Raghu, Anjanapura V. (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Fischer-Tropsch (FT) process has great potential to accomplish energy security but also for utilizing greenhouse gases to address the energy problem. Different kinds of feedstocks like coal, biomass (via gasification), CO2, methane (via reforming), and nonconventional energy sources are used to obtain the syn-gas (CO and H-2). The formation of hydrocarbons in the FT process follows ASF distribution over the majority of the catalysts. It can be overcome by the application of a suitable catalyst, controlling the active metal interaction with the support and interaction of formed hydrocarbon with the support. The ratio of syn-gas is important to maintain the desired conversion and to have more selectivity towards C5+ products. Increase in the H-2: CO ratios in the feed increases C5+ products and methane decreases. Whereas with the decrease in the ratios increases undesirable reactions and methane formation. In this article, we have discussed the recent literature from the viewpoint of increasing the C5+ selectivity. Support has a profound influence on product distribution. With the application of suitable support and controlling the interaction of the active sites yields the good CO conversion with fewer lighters and higher C5+ hydrocarbons. (c) 2019 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: HYDROCARBON PRODUCT DISTRIBUTION; CO HYDROGENATION; IRON NANOPARTICLES; ENHANCED STABILITY; HYBRID CATALYSTS; AL2O3 PROMOTER; SELECTIVITY; SYNGAS; CARBON; HYDROCRACKING